The Effect Of Proctor Supervision Model On Nurses' Compliance Level In Performing Wound Care According To SOP (Standard Operating Procedure) In Flamboyan 5 Surgical Inpatient Ward At Dr. Moewardi Regional General Hospital - Warih Tri Mulyanto; Faisal Ardian Oktavia; Farhatul Balighoh; Chalista Ayu Fatiha (Indonesian Basic and Experimental Health Sciences, 2026)
Introduction Nurse compliance with wound care procedures remains a challenge in ensuring patient safety, particularly in surgical wards that require precision in clinical practice (Kamil & Wardhani, 2020; Wang & Lee, 2020). Inconsistent adherence to standard operating procedures (SOPs) may increase the risk of infection and affect the quality of nursing services. Therefore, effective supervision is required to improve compliance in clinical practice. Objective This study aimed to analyze the effect of the Proctor supervision model on nurses’ compliance in performing wound care according to standard operating procedures in the Flamboyan 5 Surgical Inpatient Ward at Dr. Moewardi Regional General Hospital. Method This study used a quasi-experimental design with a pre-test and post-test approach without a control group. A total of 19 nurses were selected using the total sampling technique. Data were collected using a Guttman scale observation sheet consisting of 26 wound care procedure indicators. Data were analyzed using univariate and bivariate methods. Because the data were not normally distributed, the Wilcoxon Signed Rank Test was used to examine differences in compliance scores before and after the intervention. Results Before supervision, all respondents (100%) were categorized as partially compliant. After the Proctor supervision intervention, seven nurses (36.8%) were categorized as compliant, while twelve nurses (63.2%) remained partially compliant. Statistical analysis showed a significant difference between pre- and post-intervention compliance scores (p < 0.05). Conclusion The Proctor supervision model can be considered a useful strategy to improve nurse compliance in wound care practice and to support patient safety and nursing care quality.